Roman South Pannonia in the Time of St. Martin of Tours - Gračanin, Hrvoje (2008)
The paper is intended to outline the principal historical processes in the territory of Roman South Pannonia, i.e. the provinces of Pannonia Savia and Pannonia Secunda in the time of St. Martin of Tours (second half of the 4th century AD). The study deals with the overall political, military and economic situation in Southpannonian region, and it endavours to illuminate certain points about St. Martin's early life and activity (Appendix).
Rad je u istom zborniku objavljen i u prijevodu na slovenski jezik, str. 45-67.
Projekt MZOS
Projekt MZOS
ENG